Aspectos clássicos da eletrodinâmica de Maxwell suplementada pelo termo CPT-par do setor de gauge do Modelo Padrão Estendido - Pinheiro, Paulo Rogério Dias (2009)
The possibility of spontaneous breaking of Lorentz symmetry in the context of string theory appeared in 1990´s as an element capable to direct new ways for developing physics at Planck scale. Possible breaking of Lorentz invariance is seen as a characteristic of the physics beyond the usual Model Standard, that forbids such breaking in its structure. The observation of Lorentz breaking (LV) at lower energies can be seen as an evidence of occurrence of Lorentz spontaneous breaking at Planck scale, with important consequence for the development of the quantum gravitation theory. This work aims at studying the LV effects in a regime of low energies, more necessarily in the context of the Maxwell electrodynamics, in the presence of the CPT-even term (W∝υρφF∝υFρφ) of the standard model extension. In the first part of the work, we deal with the electrodynamics stemming from the parity-odd sector of the tensor W∝υρφ, where the electric and magnetic sectors are connected by the breaking parameter (violating vector k). The method of Green is then used to yield the classic solutions for this electrodynamics. It is observed that Lorentz-violating coefficients contribute in first order for the electric and magnetic sectors. An experiment of feasible accomplishment in laboratory is considered for stipulating an upper bound for the background magnitude (k < 10−16). In the sequel we deal with the electrodynamics stemming from the parity-even sector of the tensor W∝υρφ. The solutions for the electric and magnetic sector are attained similarly by the Green method. With such solutions, we are able to impose an upper bound on the parameters: (eκe−)ib < 2.9 × 10−20. Finally, we evaluate the gauge propagator of this theory, both for the parity-even and the parity-odd sectors. We then use it to analyze the stability, causality and unitary of this model. Keywords: Maxwell electrodynamics, Lorentz symmetry, Classical solutions,